Unpacking the post-lockdown employment recovery of young women in the Global South - Scott, D; Freund, R; Favara, M; Porter, C; Sánchez, A (IZA Institute of Labor Economics, 2021)
This paper analyses the difference in short-term employment recovery between young men and women in India, Peru and Vietnam following the national lockdowns imposed in all three countries during 2020. We employ a mediation model to establish whether - and to what extent – commonly suggested mechanisms are responsible for a relatively slower recovery among young women and an increase in the gender employment gap. In line with the literature, we find evidence that the unequal distribution of caring responsibilities explains a meaningful proportion of the disparity in Peru and Vietnam, but a smaller share of the change in the employment gap in India. Contrary to the previous literature, however, we find little evidence that the work activity performed before the pandemic explains the slower female recovery in any of the three study countries.